2018
DOI: 10.1128/aem.01628-18
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Fungal Polyphenol Oxidase with Chlorophenol Bioremediation Potential: Characterization and Protein Engineering

Abstract: A novel fungal PPO was heterologously expressed and biochemically characterized. Construction of single and double mutants led to the generation of variants with altered specificity against CPs. Through this work, knowledge is gained regarding the effect of mutations on the substrate specificity of PPOs. This work also demonstrates that more potent biocatalysts for the bioremediation of harmful CPs can be developed by applying site-directed mutagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 77 publications
(129 reference statements)
4
23
0
6
Order By: Relevance
“…In accordance with the predicted glycosylation sites performed in previous study (20), the crystal structure of full-length TtPPO revealed three N-glycosylation sites: Asn197 (one N-acetylglucosamine-NAG), Asn216 (NAG) and Asn259 (NAG-NAG) (Fig. 3A).…”
Section: Crystal Structure Of Ttppo-gn (Variant G292n)supporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with the predicted glycosylation sites performed in previous study (20), the crystal structure of full-length TtPPO revealed three N-glycosylation sites: Asn197 (one N-acetylglucosamine-NAG), Asn216 (NAG) and Asn259 (NAG-NAG) (Fig. 3A).…”
Section: Crystal Structure Of Ttppo-gn (Variant G292n)supporting
confidence: 89%
“…The relevant region in AoCO4 has an insertion of several amino acids (residues 216-224) and is more tilted towards the active site (Fig. 5A, highlighted Even though the third disulfide bond which is absent in TtPPO-GN has been suggested to stabilize two long loops in AoCO4, the two enzymes share similar thermostability, as shown by previously published biochemical data (20).…”
Section: Comparison With Other Ppo Structuressupporting
confidence: 72%
See 1 more Smart Citation
“…Dessa forma, há interesse crescente na maioria das pesquisas em isolar e caracterizar novas fitases de ocorrência natural que possam contemplar as características desejadas para se obter um processo biotecnológico de alta produção e baixo custo (ZHANG et al, 2010;SINGH;SATYANARAYANA, 2011;SREEDEVI;REDDY, 2012;NUGE et al, 2014). (BERKA et al, 2011;SINGH, 2014;XU et al, 2015;GU et al, 2018;NIKOLAIVITS et al, 2019) Além de enzimas termoestáveis, M. thermophila também produz uma variedade de biomoléculas, incluindo: tiol, inibidores de proteases,…”
Section: Fatores Que Influenciam a Atividade Das Fitasesunclassified
“…Enzimas produzidas por estes microrganismos apresentam grande potencial de aplicação industrial(BERKA et al, 2011;SINGH, 2014;SINGH, 2016), uma vez que podem ser estáveis em temperaturas entre 70 a 80°C (LI; LI; PAPAGEORGIOU; 2011;BERKA et al, 2011;SINGH, 2014;SINGH, 2016). thermophila (sinônimo Sporotrichum thermophile) é um fungo termofílico, filamentoso que foi recentemente reposicionado no gênero Thermothelomyces(MARIN-FELIX et al, 2015;NIKOLAIVITS et al, 2019). É amplamente distribuído na natureza com grande habilidade para secretar enzimas extracelulares acima de 45°C, tais como celulases, lacases, xilanases, pectinases, lípases e fitases (SINGH, 2014).Análises em seu genoma e dados experimentais têm sugerido que esse organismo é capaz de hidrolizar quase todos os polissacarídeos presentes na biomassa, com características diferenciadas, tais como estabilidade em temperaturas elevadas, tornando este fungo um excelente candidato a biorefinaria de produtos químicos e biocombustíveis, a partir de fontes renováveis de carbono…”
unclassified